AKM-Based Formative Assessment Instrument for Evaluating Critical Thinking Skills in Thermochemisty Learning - Aryka Khulayda Mardhatilla; Rudiana Agustini (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
To support the Independent Curriculum and meet 21st century learning expectations, it is critical to design an assessment system that can measure high-level thinking skills. One of the main challenges is the limited availability of formative assessments based on the Minimum Competency Assessment (AKM) that specifically evaluate critical thinking skills in thermochemistry. The goal of this project is to create a formative assessment tool based on the AKM framework that has strong validity and reliability for assessing the thermochemistry-related critical thinking abilities of eleventh-grade high school students. The ADDIE model served as the guiding framework for the development process. Three professional validators assessed the instrument's theoretical validity, while a sample of 34 eleventh-grade students from SMA Hang Tuah 1 Surabaya participated in empirical testing. The findings reveal that the instrument attained an exceptionally high level of theoretical validity, evidenced by content validity of 93.3%, construct validity of 100%, and language validity of 100%. A Cronbach's Alpha coefficient of 0.950 demonstrated the exceptional reliability and empirical validity of all 20 items. The majority of the items on the test were classified as moderately difficult and had a high capacity for discrimination, demonstrating the instrument's good qualitative qualities.